Receptive Fields of Retinal Bipolar Cells Are Mediated by Heterogeneous Synaptic Circuitry - Zhang, Ai-Jun; Wu, Samuel M (The Journal of neuroscience, 2009)
Center-surround antagonistic receptive field (CSARF) organization is the basic synaptic circuit that serves as elementary building blocks for spatial information processing in the visual system. Cells with such receptive fields converge into higher-order visual neurons to form more complex receptive fields. Retinal bipolar cells (BCs) are the first neurons along the visual pathway that exhibit CSARF organization. BCs have been classified according to their response polarities and rod/cone inputs, and they project signals to target cells at different sublaminae of the inner plexiform layer. On the other hand, CSARFs of various types of BCs have been assumed be organized the same way. Here we examined center and surround responses of over 250 salamander BCs, and demonstrated that different types of BCs exhibit different patterns of dye coupling, receptive field center size, surround response strength, and conductance changes associated with center and surround responses. We show that BC receptive field center sizes varied with the degree of BC–BC coupling, and that surround responses of different BCs are mediated by different combinations of five lateral synaptic pathways mediated by the horizontal cells and amacrine cells. The finding of heterogeneous receptive field circuitry fundamentally challenges the common assumption that CSARFs of different subtypes of visual neurons are mediated by the same synaptic pathways. BCs carrying different visual signals use different synaptic circuits to process spatial information, allowing shape and contrast computation be differentially modulated by various lighting and adaptation conditions.